Magnesium, the biological significance of magnesium as a biogenic element - Marjona, Mardiqulova; Rakhmonovich, Karjavov Abdikhakim (American Journal of Biomedicine and Pharmacy, 2025)
Magnesium is an essential mineral for the human body that supports the health of bones, muscles, the nervous system, and the heart. It participates in energy production, helps regulate blood pressure, reduces stress, and is mainly obtained from green vegetables, nuts, and grain products. Magnesium deficiency may lead to muscle cramps, insomnia, irritability, and other disorders; therefore, sufficient intake through diet or supplements is important. Vitamin B₆ improves the absorption of magnesium and facilitates its entry into cells.